THE SOCCER PASSION AND THE SECRETS OF THE BAIXADINHA: A VIEW BY THE SYSTEMIC PERSPECTIVE. (Fiep Bulletin - online, 2011)
This study was a descriptive and historical report seeks to build through the habits and rituals of day-to-day work and sports, soccer passion lived since childhood in Baixadinha, small field located in vila de Segredo, city at RS, Brazil, as a contribution to the construction of identities and professional choices. Descriptive research is defined by Cervo and Bervian (1996) as that which observes, records, analyzes phenomena or facts without manipulating them. Identities are constructed from various fragments in order to obtain a structured view of reality between work and family soccer game, a systemic approach, according to Capra. The story, such as lifetime, is consolidated into single spaces, in a daily life of family and society and man and nature. It has been the experience systemic, maintenance and disputes in Baixadinha divided the space with cattle, the observation of the amateur team from the village, in games and school in career choices. The "web of life" translates into interdisciplinarity as a way of overcoming and building core knowledge among teachers, interacting popular knowledge with scientific knowledge.
Keywords: soccer; systemic and identity construction